2018
DOI: 10.1007/s11030-018-9870-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic applications and methodology development of Chan–Lam coupling: a review

Abstract: Chan-Lam coupling is one of the most popular and easy methods to perform arylation of amines (N-arylations). This cross-coupling is generally performed by reacting aryl boronate derivatives with a variety of substrates involving nitrogen containing functional groups such as amines, amides, ureas, hydrazine, carbamates. This article summarizes the synthetic applications of this reaction and the efforts of scientists to develop novel and efficient methodologies for this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 79 publications
2
50
0
Order By: Relevance
“…It was observed that when the Cu(OAc) 2 equivalents were less than one, the reaction did not proceed to completion. This result is in line with most Chan-Lam coupling procedures in the literature, [37] where a stoichiometric amount of copper is required. Overall, the optimised conditions were determined to be 1 eq.…”
Section: Resultssupporting
confidence: 89%
“…It was observed that when the Cu(OAc) 2 equivalents were less than one, the reaction did not proceed to completion. This result is in line with most Chan-Lam coupling procedures in the literature, [37] where a stoichiometric amount of copper is required. Overall, the optimised conditions were determined to be 1 eq.…”
Section: Resultssupporting
confidence: 89%
“…Air is routinely used for the reaction as an oxidant. The CEL coupling later was elaborated to allow C−N, C−O, C−S, C−Se, C−P bond formation via copper(II)‐catalyzed pathways of arylboronic acids with a wide range of nucleophiles, including sensitive substrates, which is critically important in numerous commercial chemical processes . There are several reports for three‐component, tandem CEL‐type reactions and heterocycles synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…Organoboron compounds have been recognized as extremely useful and readily accessible synthetic intermediates in organic synthesis for many decades -from Nobelprize-winning works of Brown on organoboranes, 1,2 to palladium-catalyzed reaction of boronic acids developed by Suzuki (also awarded with the Nobel prize) 3,4 and more recent discoveries like Chan-Lam 5 and radical photoredox couplings of trifluoroborates. 6 Much attention has been given to the increasing utility of organoboron compounds as building blocks in the construction of complex molecules (for recent general reviews, see [7][8][9][10] ).…”
Section: Introductionmentioning
confidence: 99%